Intrinsic Motivation Organizational Support Commitment and OCB in Rural Banking: Motivasi Intrinsik, Dukungan Organisasi, Komitmen, dan Perilaku Organisasi yang Baik (OCB) dalam Perbankan Pedesaan - Anisa Lukitasari; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Banking institutions require employee behaviors that exceed formal job descriptions to maintain service quality and organizational sustainability. Specific Background BPR Delta Artha Perseroda faces challenges related to low Organizational Citizenship Behavior among employees, reflected in limited cooperation, initiative, and participation. Knowledge Gap Previous studies have examined intrinsic motivation, organizational support, and organizational commitment separately, yet empirical evidence testing these variables simultaneously within rural banking institutions remains limited. Aims This study aims to examine the relationships between intrinsic motivation, organizational support, and organizational commitment with Organizational Citizenship Behavior at BPR Delta Artha Perseroda. Results Using a quantitative approach with multiple linear regression on 80 employees, the findings show that intrinsic motivation, organizational support, and organizational commitment each demonstrate significant relationships with Organizational Citizenship Behavior, with intrinsic motivation showing the strongest contribution. Novelty The study provides integrated empirical evidence from a rural banking context by analyzing these three variables concurrently within a single organizational setting. Implications The findings offer practical insights for human resource management in rural banks to strengthen internal motivation, organizational support mechanisms, and employee commitment in fostering positive discretionary workplace behaviors. Keywords: Intrinsic Motivation, Organizational Support, Organizational Commitment, Organizational Citizenship Behavior, Rural Banking Key Findings Highlights: Employee internal drive shows the strongest association with discretionary workplace behavior. Organizational assistance perceptions align with voluntary cooperative actions. Emotional attachment to the institution supports sustained employee contribution.